Is climatic regionalization in frame of estimated pedologic-ecological system actual in 21st century? - STŘEDOVÁ, Hana; CHUCHMA, Filip (Contributions to Geophysics and Geodesy, 2014)
Climatic variables defining climatic regions of estimated pedologic-ecological system (EPEU) were calculated based on fifty-year climatic data from 1961 to 2010. Obtained results were subsequently compared to intervals determining individual climatic regions defined by previous climatic data (1901–1950). In many agricultural intense areas sum of air temperature and mean air temperature exceeded upper limit. In terms of precipitation it is especially noticeable in the wet (higher) altitudes. Significant volatility was found for probability of dry periods from April to September. The values of the moisture certainty from April to September for the period 1961–2010 reached to several tens. In the final analysis, the only safe prediction is that the present and future are likely to be very different from the past. It is necessary to take it into account for actualization of EPEU methodology. Among the strongest arguments justifying the need of this actualization is in particular climate development since 1901, technological progress and improved measurement technology as well as automation and development of climate models coupled with simulations of complex characteristics and estimates of future climate. It is evident that the development of climate and other factors have an enormous impact on soil fertility. This should be also taken into consideration when fixing the official price. It is necessary to consider the possible replacement of the existing characteristics by more suitable (for example soil moisture balance). The findings might be summarized in few words: old climatic regions do not reflect actual climatic conditions.